IMPLIKASI PRINSIP FAIR USE SEBAGAI PENYEIMBANG EKSKLUSIVITAS HAK KEKAYAAN INTELEKTUAL DENGAN ANTI MONOPOLI - Azzahra Wida Be Paradita (Fakultas Hukum Universitas Udayana, 2023)
The objective of this research is to examine the contradiction between the exclusivity of intellectual property (IP) and anti-monopoly law, utilizing the fair use principle as a balancing mechanism to facilitate a more harmonious and complementary regulation of business practices in Indonesia. Employing the normative juridical method, the researcher collected relevant legal materials and conducted a descriptive analysis to demonstrate that IPR objects, which are exceptions in Law Number 5 of 1999, effectively suppress and exclude economic business activities in Indonesia. The study's results also reveal that this disparity forces business actors in Indonesia to miss the opportunity for fair and healthy competition with well-known foreign products (wellknown mark). Researchers propose the idea that the principle of fair use, presents a solution that can provide balance for the coexistence of IPR and anti-monopoly regulations.